Development and pilot testing of an online intervention to support young couples' coping and adjustment to breast cancer. (29th January 2014) - Fergus, K.D.; McLeod, D.; Carter, W.; Warner, E.; Gardner, S.L.; Granek, L.; Cullen, K.I.
<x xml:space="preserve">Abstract</x> Couplelinks is an original, professionally facilitated online intervention tailored to the unique challenges facing young women with breast cancer and their male partners. The purpose of this evaluation was to determine the feasibility and acceptability of the intervention and areas for improvement. Sixteen couples were sequentially enrolled over an 18‐month period. Couples provided feedback via a treatment satisfaction survey, and post‐treatment interviews with a sub‐group of participants. Qualitative information was analysed for themes relevant to the program's acceptability, perceived benefits and limitations, and directions for improvement. Of the 16 couples who enrolled, six completed four modules or less, and 10 completed the entire program. Completers reported satisfaction with the program overall, as well as with the website useability and professional facilitation. Reported benefits were: enhanced communication and self‐other knowledge; creation of opportunities for meaningful, cancer‐related discussion; affirmation of relationship strengths; and a greater sense of closeness between partners. The main reported limitation was how program participation disrupted the couple's usual routine. Themes related to non‐completion suggest that partners with particularly elevated relational or illness‐related distress, or with differential levels of motivation, are less likely to finish. These findings have led to targeted improvements to the website and intervention protocol.